Al-DirᾹsah Al-TahlῙliyyah Li MuhtawᾹ Al-KitᾹb Al-MadrasῙy Li Ta’lῙm Al-Lugah Al-’Arabiyyah FῙ Al-Marhalah Al-ṠᾹnawiyyah ’AlᾹ AsᾹs Cefr (Al-Iṭar Al-Marja’Ῑ Al-Aurubbiy Al-Musytarak) - Arif Taufikurrohman; Imam Asrori; Abdul Wahab Rosyidi (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2022)
معرفة مستوى محتوى كتاب تعليم اللغة العربية في المرحلة الثانوية العامة من الأمور المهمة لأنها تكون منطلقا في إعداد مادة تعليم اللغة العربية في المرحلة الجامعية. وبدون معرفة المستوى قد يقع التكرار في تحديد مستواها ويؤدي إلى تأخر الارتقاء بالمستوى اللغوي إلى المستوى الأعلى. وتهدف هذه الدراسة إلى تحليل وصف محتوى الكتاب المدرسي في المرحلة الثانوية على أساس الإطار المرجعي الأروبي المشترك. وسلك الباحث في كتابة هذا البحث المنهج الوصفي بحيث يصف محتوى الكتاب ويحللها ثم يقيسها على أساس الإطار المرجعي الأوروبي المشترك (CEFR) لمعرفة المستوى اللغوي من هذا الكتاب المدرسي. وتوصل الباحث في هذا البحث إلى النتائج التالية: أولا، أن محتوى الكتاب المدرسي الأول في المرحلة الثانوية العامة للفصل العاشر يكون بين مستويات A1 و A2و B1؛ وثانيا، أن الكتاب الثاني والثالث يترددان بين مستويين، هما: B1 و B2 من المستويات اللغوية Knowing the level of content of Arabic textbooks at the high school level is important because it is the starting point in preparing Arabic teaching materials at the university level. Without knowing the level, repetition can occur in determining the level and cause delays in increasing the linguistic level to a higher level. The purpose of this study was to analyze the description of the content of textbooks at the general secondary level based on the Common European Terms of Reference. In writing this research, the researcher used a descriptive approach to describe the contents of the book, analyzed it and then measured it based on the Common European Framework of Reference (CEFR) to determine the language level of this textbook. In this study, the researcher achieved the following results: First, the contents of the first textbook at the general secondary level for the tenth semester were at levels A1, A2, B1, and secondly that the second and third books echoed between two levels, namely: B1 and B2 language level.